HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN BERAT BADAN IBU MENYUSUI DI POLINDES TERATAI DESA JAMPIROGO KECAMATAN SOOKO KABUPATEN MOJOKERTO - Permata Sari, Dyah (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Exclusive breastfeeding is the only breast feeding her baby at birth until the age of 6 months without food and other beverages. Factors affecting the increase in maternal weight mothers not breastfeed their babies exclusively to the mother to be fat.This type of observational study is analytic. The study design was cross sectional. Population of mothers breastfeeding over 6 months in May 2015 with a total of 38 nursing mothers. Sampling technique used in this study is probability sampling with simple random sampling method obtained 35 respondents. Data collection using a closed questionnaire. The research was conducted on May 27 until May 28, 2015. Data analyzed by chisquare test.Results showed respondents a number of 35 respondents, most respondents are exclusively breastfed are 23 respondents (67.5%), most respondents have a BMI in the normalcharacteristics (>18.5 to 25.0) as many(60%).Analysis of data obtained using the chisquare test calculations with significant value = 0.000, while α = 0.05. Therefore significantly smaller value of α = 0.05 then H0 rejected H1 is accepted meaning there is a relationship.Concluded that many respondents who give exclusive breastfeeding for 6 months of normal weight.Health professionals should retain and motivate breastfeeding mothers by providing counseling and distributing leaflets to the respondent to prepare exclusive breastfeeding to the maximum.Key words: Exclusive Breastfeeding, Weight Gain, Mother, Breastfeeding